2016
DOI: 10.12659/ajcr.895415
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Superb Micro-Vascular Ultrasound Imaging (SMI) and Contrast-Enhanced Ultrasound (CEUS) for Detection of Endoleaks After Endovascular Aneurysm Repair (EVAR)

Abstract: Patient: Male, 68Final Diagnosis: Unusual clinical courseSymptoms: NoneMedication: —Clinical Procedure: Angio CTSpecialty: SurgeryObjective:Challenging differential diagnosisBackground:High-resolution contrast-enhanced ultrasound is one of methods used in the detection and characterization of endoleaks, which is a frequent complication after EVAR. A new technology provided by Toshiba’s AplioTM 500 ultrasound system, called Superb Micro-Vascular Imaging (SMI), is dedicated specifically to imaging very low flow … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 4 publications
1
25
0
Order By: Relevance
“…The first case report about the use of SMI for EVAR surveillance comes from our research team; we demonstrated promising results of using SMI for endoleak detection, comparing the method with CDUS, CEUS, and CTA [4]. Cantisani et al compared SMI with CDUS, CEUS, and CTA.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…The first case report about the use of SMI for EVAR surveillance comes from our research team; we demonstrated promising results of using SMI for endoleak detection, comparing the method with CDUS, CEUS, and CTA [4]. Cantisani et al compared SMI with CDUS, CEUS, and CTA.…”
Section: Discussionmentioning
confidence: 96%
“…Other potential clinical applications of SMI include gynecological and obstetric imaging, evaluation of lymph nodes and abdominal areas, as well as diagnosis of skin lesions, rheumatoid arthritis, and many other medical conditions [4, 5, 13, 27, 28]. …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Superb microvascular imaging (SMI), a novel technique for displaying very low‐velocity blood flow, allows imaging of microvessels in any location without ultrasound contrast agents at present . Compared with CEUS in the observation of neovascularization in early osteoanagenesis, SMI is simpler and more economical, which is conducive to repeated examination . In the present study, we established an osteoanagenesis model and used the SMI technique and CEUS to observe the neovascularization in early osteoanagenesis.…”
mentioning
confidence: 99%